(untitled) (Canadian Journal of Native Studies, 2026)
Abstract Through a systematic content analysis of mainstream print media treatment of two Supreme Court rulings on Indigenous treaty entitlements, this research examines attributes of the coverage afforded to Indigenous and non-Indigenous voices. Our findings demonstrate that, with respect to narrative power, non-Indigenous interests and perspectives were predominantly represented by mainstream print media. Non-Indigenous voices were given priority and garnered more lines of direct quotation. Further, the qualitative analysis demonstrates that the mainstream print media coverage emphasised concerns about Indigenous Peoples’ abilities to manage resources competently and responsibly, while centering on the potential implications of Indigenous sovereignty over their territory and resources for dominant class non-Indigenous economic interests. Lastly, this research argues, through the conceptual/theoretical lens of “cultural hegemony” and “cognitive imperialism,” that mainstream print media function to legitimate the dominance of settler ideology and economic interests, through the conscious representation of Indigenous treaty rights as antithetical to Eurocentric interests and the predominant social order. We argue that the data show a systemic bias, which functions as a key mechanism for the domination, control and suppression of Indigenous Peoples.